Increasing Local Own-Source Revenue through The Development of The Regional Tourism Sector - Harries Madiistriyatno; Ida Musdafia Ibrahim; Dudung Hadiwijaya (Universitas Muhammadiyah Tangerang, 2020)
The tourism sector is one important sector that can contribute to improving the regional economy. However, the implementation of product and tariff strategies that are not optimal can have an impact on the low sales value and profits, and in turn affect regional revenues. This study aims to analyze the effect of product strategy performance, tariff strategy and sales value on profits. Using a quantitative approach, the population in this study is 20 tourist destinations in DKI Jakarta Province. Primary data were obtained through questionnaires and interviews, while secondary data were obtained through documents and related literature. The data analysis technique used is path analysis. The results of this study indicate product strategy, tariff strategy, and sales value have a partial and simultaneous effect both on profit. The dominant variables in this study are (1) the application of the tariff strategy as a determinant of sales value and (2) the application of the product strategy as a determinant of profit.Sektor pariwisata merupakan salah satu sektor penting yang bisa berkontribusi bagi peningkatan perekonomian daerah. Namun demikian, penerapan strategi produk dan tarif yang tak maksimal dapat berdampak pada rendahnya nilai penjualan serta laba yang diperoleh, dan pada gilirannya memengaruhi penerimaan daerah. Penelitian ini bertujuan untuk menganalisis pengaruh kinerja strategi produk, strategi tarif dan nilai penjualan terhadap laba usaha. Menggunakan pendekatan kuantitatif, populasi dalam penelitian ini adalah 20 destinasi wisata di Propinsi DKI Jakarta. Data primer diperoleh melalui kuesioner dan wawancara, sementara data sekunder diperoleh melalui dokumen dan literatur-literatur terkait. Teknik analisis data yang digunakan adalah path analysis. Hasil penelitian ini menunjukkan strategi produk, strategi tarif, dan nilai penjualan berpengaruh secara simultan terhadap laba. Variabel dominan dalam penelitian ini ialah (1) penerapan strategi tarif sebagai determinan penjualan dan (2) penerapan strategi produk sebagai determinan laba.